Entomopathogen-based biopesticides: insights into unraveling their potential in insect pest management - Irsad,; Shahid, Mohammad; Haq, Ejazul; Mohamed, Abdullah; Rizvi, Parvez Qamar; Kolanthasamy, Elango (Frontiers in Microbiology, 2023)
Global food security is a critical challenge to fulfil the demands of an exponentially growing population. So far, growers rely on chemicals; the broad-spectrum application of synthetic molecules lead to environmental contamination, resistance development, residual toxicity, pest resurgence, and detrimental effect on human health and cattle, etc. Crop production needs to be improved with environmental and human health concerns to ensure food security. Furthermore, economically important crops are prone to attack by insect pests, causing considerable yield losses. Microbes are an eco-friendly, versatile alternative and a potential candidate for combatting destructive pests below the economic injury level and improving the plant's health and productivity. Several microbial pathogens, including parasites, predators, parasitoids, pollinators, and many beneficial microorganisms, possess toxic properties against target organisms but do not cause harm to the non-target organisms. ENMs have great potential for pest suppression due to their remarkable properties. Bacteria are host-specific, fungi have a broader host range, and they may significantly be affected by both soil-dwelling and terrestrial insect pests. Virulent pathogens cause mortality in target insect pests known as entomopathogens (ENMs) and can penetrate through natural openings, ingestions, and integuments to cause a possible effect on target insect pests. The objective of using ENMs is to sustain productivity, improve environmental health, reduce pesticides, and conserve natural resources. Moreover, research is still going on to discover the other possible aspects, especially exploring the potential entomopathogens. Therefore, there is a need for identification, isolation, and bioformulation to overcome the existing issues. This manuscript is mainly focused on the status of bio-formulations, pathogenicity, their mode of action, and the potential application of different types of microbial formulations for sustainable pest management.